Algorithms for coherent diversity combining of M-ary orthogonal signals. - Thompson, J.S.
This paper discusses the use of coherent demodulation for antenna array receivers employing direct sequence spread spectrum techniques and M-ary orthogonal modulation. Three different approaches are discussed. The first is a conventional receiver using training sequences and decision feedback for channel estimation. The other two techniques employ decisions from a simple noncoherent combining (O) receiver to circumvent the need for training sequences. The bit error ratio (BER) performance of coherent M-ary orthogonal modulation is derived. Some qualitative analysis is also presented for the algorithms, and simulation results are used to compare their performance in different scenarios
Keywords: BER performance; DS/CDMA.; M-ary orthogonal modulation; M-ary orthogonal signals; Antenna array receivers; Bit error ratio; Cellular systems; Channel estimation; Coherent M-ary orthogonal modulation; Coherent demodulation; Coherent diversity combining algorithms; Decision feedback; Direct sequence spread spectrum; Mobile transmitter; Multipath components; Noncoherent combining receiver; Receiver; Simulation results; Training sequences